In vitro micropropagation of Tinospora cordifolia (Willd.) Miers from shoot tip explants - Mridula, Krishna Reddy; Parthibhan, Selvaraju; Kumar, Tiruppathi Senthil; Rao, Adhikarla Suryanarayana; Rao, Mandali Venkateswara (Agriculture and Natural Resources, 2019)
An efficient in vitro micropropagation protocol from shoot tip explants was established for Tinospora cordifolia (Willd.) Miers. Young and mature shoot tip (YST and MST, respectively) explants from two different-aged plant sources (15 d and 3 yr) were treated simultaneously to develop and compare their efficacy in the micropropagation protocol. Among the cytokinins and synergetic treatments, 6-benzyladenine (BA; 2.0 mg/L) and kinetin (KN; 1.0 mg/L) responded better in bud break and shoot development, at both individual concentrations and in combination. Addition of the auxin indole-3-acetic acid (IAA; 0.5 mg/L) to the optimal cytokinin concentrations of BA (2.0 mg/L) with KN (1.0 mg/L), enhanced multiple shoot induction and shoot growth. Further supplementation of gibberellic acid (0.1 mg/L) and an antioxidant (ascorbic acid at 100 mg/L) significantly enhanced the shoot bud induction, shoot number and shoot length. Assessment of different basal media using the best plant growth hormone complex confirmed that the Murashige and Skoog (MS) medium best supported shoot bud break and shoot development in both the shoot tip explants. The best rooting response was from half-strength MS medium fortified with indole-3-butyric acid (0.5 mg/L), resulting in approximately 80% of the plantlets successfully acclimatized both at in vitro and in vivo conditions. In conclusion, the YST explants responded better than the MST explants in all aspects of growth and development and proved that t